Students' Creative Thinking Skills in Solving Three-Variable Linear Equation System (SPLTV) Problems: A Gender Perspective - Azizah, Lailatul Nur; Putri, Anggita Oktaviana (Desimal: Jurnal Matematika, 2026)
Creative thinking is essential in mathematics because it enables students to generate varied, flexible, and original solutions to non-routine problems. This study investigated students’ creative thinking skills in solving Three-Variable Linear Equation System (SPLTV) problems from a gender perspective. A qualitative descriptive design involved 15 eleventh-grade students from a State Islamic Senior High School in Malang Regency, Indonesia. Data were collected through two open-ended SPLTV tasks and interviews. Five focal participants were selected purposively based on gender and creative-thinking ability categories. Their written responses and interview explanations were analyzed using the indicators of fluency, flexibility, and novelty, supported by data reduction, data display, conclusion drawing, and technique triangulation. The findings showed that all participants demonstrated fluency by producing several correct alternatives. However, flexibility and contextual novelty were identified only in the high-ability female participant, who used both elimination and matrix determinant methods. Male and female participants in the moderate and low categories showed similar patterns, as they could generate multiple answers but relied on one familiar strategy and did not produce a distinct approach. These results indicate that creative-thinking dimensions do not necessarily develop simultaneously and that ability level, strategic knowledge, and experience may be more influential than gender alone. The study provides a contextualized account of mathematical creativity in open-ended SPLTV problem solving and highlights the value of instruction that promotes comparison, justification, and evaluation of multiple solution methods.